First Language Interference On English Use - Pebri Prandika Putra (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
This study aimed to investigate and analyze in depth about first language interference on English use of First Year Students at Senior High School in Bengkulu City. The research method was Qualitative Descriptive. This research is able to capture and provide the description clearly of a language phenomenon that is the object of study. The study was conducted in 4 high schools in Bengkulu city such as SMAN 7, MAN 2, SMKS 11 Serunting 2 and SMA Pembangunan. The data was analyzed totaling 30 data and completed with a questionnaire test. The results of the study were conducted by testing 5 types of interference namely lexical interference, semantic interference, idiomatic interference, collocation interference and cultural interference. From 30 data that investigated and analyzed showing 80% of errors occurred at the level of lexical interference, 5% semantic interference, 10% collocation interference, 5% cultural interference and 0 % idiomatics interference. Lexical interference is more dominant in this study because the mastery of the first language is more dominant in the process of learning foreign language. Key words: Language, Interference